Review on Security Of Peer To Peer & Client-Server Network Using XOR Metrics In Cloud Computing - *, Rekha1; Kumar, Mahesh (IJRDO -Journal of Computer Science Engineering, 2017)
Peer-to-peer networks are less secure than a client-server network because security is handled by individual computers, noton network as a whole. Resources of computers in network could become overburdened as they have to support not only workstationuser, but also requests from network users. Within XOR-based metric we provide consistency & performance, latency minimizingrouting, & a symmetric, unidirectional topology to peer to peer & client server cloud. Cloud based services & service providers are beingevolved which has resulted in a new business trend based on cloud technology. Cloud Computing is a architecture that server resourceson distributed scalable platform so as to provide on demand computing resources & services. Cloud service providers offer cloud platformsfor their customers to use & create their web services, much like internet service providers offer costumers high speed broadband to access